THE EFFECT OF FACEBOOK IN IMPROVING STUDENT’S IDENTIFICATION OF EXPLICIT MEANING IN READING COMPREHENSION - Lailatus Sa'adah; Chalimah M.Pd (STKIP PGRI Jombang, 2015)
This report presents the results of a study that examined the efficiency of professional development for teachers using Facebook with respect to improving student reading skills. To achieve this purpose, a quasy experimental study was conducted in 2014 A-2014 B to determine the extent to which Facebook affected teacher practices and student achievement in reading comprehension. The study examined trustworthiness of implementation through project based learning using Facebook conducted outside the classroom to determine the extent to which teachers implemented the desired strategies and to describe differences between classroom practices of teachers in the treatment group and those of teachers in the control group. The finding of posttest analyzed by using Ancova which compared between two groups gain sig 0.043. It shows that sig < α (0,05) which means Facebook as media can give significant difference on students’s reading comprehension